A Minkowski difference‐based advancing front packing technique for generating convex noncircular particles in complex domains - Xia, Ming; Xu, Xin; Gong, Fengqiang; Wang, Min; Feng, Y. T. (International journal for numerical methods in engineering, 2023)
In this work, a Minkowski difference‐based advancing front approach is proposed to generate convex and non‐circular particles in a predefined computational domain. Two specific algorithms are developed to handle the contact conformity of generated particles with the boundaries of the computational domain. The first, called the open form, is used to handle the smooth contact of generated particles with (external) boundaries, while the other, called the closed form, is proposed to handle the internal boundaries of a computational domain with a complex cavity. The Gilbert‐Johnson‐Keerthi (GJK) method is used to efficiently solve the contact detection between the newly generated particle at the front and existing particles. Furthermore, the problem of one‐sided particle lifting, which can cause some defects in the packing structure in existing advancing front methods during packing generation, is highlighted and an effective solution is developed. Several examples of increasing complexity are used to demonstrate the efficiency and applicability of the proposed packing generation approach. The numerical results show that the generated packing is not only more uniform, but also achieves a higher packing density than existing advancing front methods.